Control system design guide : using your computer to understand and diagnose feedback controllers - Ellis, George (Elsevier Science, 2012)
Control Systems Design Guide has helped thousands of engineers to improve machine performance. This fourth edition of the practical guide has been updated with cutting-edge control design scenarios, models and simulations enabling apps from battlebots to solar collectors. This useful reference enhances coverage of practical applications via the inclusion of new control system models, troubleshooting tips, and expanded coverage of complex systems requirements, such as increased speed, precision and remote capabilities, bridging the gap between the complex, math-heavy control theory taught in formal courses, and the efficient implementation required in real industry settings.
Keywords: Feedback control systems -- Design and construction.; Automatic control.; System design.; Engineering.; Mechanical engineering.; elektronické knihy; electronic books